Stakeholder Satısfactıon Wıth Physıcal Infrastructure Development In Rural Areas: Sustaınable Constructıon Approach - Aryati Indah Kusumastuti; Ingrid Multirejeki; Arif Firmanto (Cita Konsultindo Research Center, 2024)
By fulfilling fundamental development objectives like creating jobs, providing for the needs of the community, and achieving sustainable and coordinated urban and rural development, physical infrastructure development in rural areas makes a substantial contribution to the overall economic development of the village. In rural areas, physical infrastructure development approaches have evolved to support sustainable development—that is, economic independence, community involvement, and environmental sustainability—as well as social and economic advancement. The overall goal of this study is to assess how well stakeholders are satisfied with the physical infrastructure built in rural areas in terms of sustainable construction practices. The study was conducted by interviewing stakeholders in rural development in Cirebon Regency. Stakeholders include local (village) and district planners, supervisors, and communities. Sustainable construction is viewed from the perspectives of economic sustainability, social sustainability, and environmental sustainability variables. The data in this study were analyzed using satisfaction index analysis and gap analysis between expectations (weighting), stakeholder assessment, and a t-test. According to the findings, the physical infrastructure development in Cirebon's rural areas has generally been met with satisfaction by stakeholders. There was no significant gap between the expectations and assessments of stakeholders in environmental, economic, and social aspects (p > 0.5). However, of the 16 indicators, there were six indicators (37.5%) that exhibited gaps.